Public Health Information Standard Data Quality and Governance - Paramita, Paramita (Riviera Publishing, 2023)
Many public health organizations face data quality challenges due to the complexity of the structure of clinical data systems, the massive growth in the volume of clinical data, and the need for more standardization between clinical systems in terms of naming and modelling. Data quality is an integral part of data governance, ensuring that data management is fit for purpose. It refers to the overall utility of a data set and its ability to be processed and analyzed quickly for other uses. This study uses a qualitative research method which is a principled research method that focuses on the description and understanding of the observed social phenomena. Moreover, the results of the study were obtained in the form of Standards for Data Quality according to the American Health Information Management Association (AHIMA) and the European Health Data Space (EHDS). In addition, there is also a discussion on privacy, security, and compliance. As well as obtaining a data governance framework for the health industry and good health industry governance. The conclusions from this study indicate that the quality of data and governance data in governance in the health industry is essential to ensure the achievement of effective and efficient health services and can be relied upon in decision-making.